The Impact of Implementing Islamic Sharia on Women's Freedom in Aceh - adami, muhammad afrizal (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to determine the impact of the implementation of Islamic Sharia on the freedom of women in the Province of Aceh, Indonesia. This research method uses a qualitative approach with a questionnaire survey as the data collection instrument. The survey is designed to collect data related to the implementation of Sharia and its impact on women's freedom. Respondents were randomly selected from various regions in Aceh. Data were analyzed using descriptive statistics. The respondents who participated in the survey were 20 women living in Aceh, aged between 17-25 years. The results of this study indicate that the implementation of Sharia has a significant impact on freedom of clothing, mobility, and access for women. This study is expected to provide comprehensive insights into the situation in Aceh.